The Additional Effect of Individualized Prescriber-Focused Feedback on General Guideline Instruction in Reducing Antipsychotic Polypharmacy in Inpatients. Issue 2 (March 2021) - Lochmann van Bennekom, Marc W.H.; Gijsman, Harm J.; Groenewoud, Hans; Verkes, Robbert-Jan
Abstract: Purpose/Background: Antipsychotic polypharmacy (APP) is the concurrent use of more than one antipsychotic by a patient. Multiple antipsychotics are often prescribed, although all relevant guidelines discourage this practice. These recommendations are based on a lack of evidence for effectiveness and an increased risk of serious adverse events with APP. Studies on the effects of educational interventions targeted at physicians have demonstrated inconclusive results. Moreover, it is unclear how individualized these interventions need to be. In this study, we aimed to assess the effect of a general intervention and the additional impact of an individualized, prescriber-focused intervention on guidelines adherence, that is, the prescription of APP. Methods/Procedures: We conducted a 36-month 2-step serial intervention study with 4 stages of 9 months each (baseline, general intervention, addition of an individualized intervention, and follow-up) including all 20 inpatient units of one regional mental health organization. The primary outcome was the proportion of patients with regular prescriptions for APP ≥30 consecutive days across all patients with a prescription of at least one antipsychotic. The secondary outcome was the proportion of patient days on APP over the total number of patient days on at least one antipsychotic. Findings/Results: The general intervention was ineffective on both outcome measures. Addition of an individualized intervention decreased the proportion of patients with prescriptions for episodes of persistent APP significantly by 49.6%. The proportion of patient days on APP significantly decreased by 35.4%. Implications/Conclusions: In contrast to a general intervention, the addition of an individualized intervention was effective in improving adherence to guidelines with respect to APP prescription in inpatients. Abstract : Supplemental digital content is available in the text.